Method for preparing functional composite paper from waste cotton textiles
Through electrostatic spinning technology, polylactic acid nanofiber membranes and cotton fibers were prepared, and antibacterial composite paper was prepared by wet lamination and hot pressing processes, which solved the problems of low recycling rate of waste cotton textiles and poor antibacterial paper effects, achieving high efficiency , environmentally friendly composite paper preparation.
Patent Information
- Application Number
- CN202411789309.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
AI Technical Summary
When the prior art uses waste cotton textiles to recycle, there are problems such as environmental pollution, waste of resources and low economic benefits of products, and the antibacterial effect of traditional antibacterial paper preparation methods is poor in durability and environmental friendliness.
Polylactic acid nanofiber membranes with antibacterial properties were prepared by electrospinning technology, and mixed with cotton fibers. Degradable composite papers with antibacterial properties were prepared by wet lamination and hot pressing.
It improves the mechanical properties and antibacterial properties of composite paper, extends the shelf life of food, reduces production costs, and is simple in process, environmentally friendly and degradable.
Smart Images

Figure CN119434028A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite paper, and in particular relates to a method for preparing functional composite paper by utilizing waste cotton textiles. Background Art
[0002] Among various natural textile fibers, cotton fiber is one of the most important textile raw materials, and at the same time, the annual consumption is also the largest. This is mainly due to the good moisture absorption and air permeability, superior feel and strength of cotton fiber. Therefore, cotton textiles, which are popular among people, also account for a large proportion of discarded textiles. According to statistics from relevant agencies, by 2030, the recycling rate of discarded textiles in China needs to reach 30%. However, at present, the actual recycling efficiency is less than 15%. Therefore, how to improve the recycling of discarded cotton fabrics is of great significance.
[0003] At present, the recycling and treatment methods of waste cotton textiles in my country are relatively simple. They are mainly generated by incineration, and the heat energy is converted into electricity to drive power equipment, or the waste cotton textiles are directly buried underground by landfill. This recycling method is simple to operate, but it has obvious disadvantages. First, incineration will release harmful gases and pollute the environment. Secondly, landfilling waste cotton textiles will occupy a lot of land resources and cause resource waste. In addition, due to the quality defects of waste cotton textiles themselves, when they are recycled and processed into new products, the products will have the disadvantages of low economic benefits and conversion rate. Although the use of chemical methods can not only efficiently recycle waste cotton textiles, but also improve their economic value, the chemical method requires a variety of complex chemical reactions, professional technology and equipment support, and also needs to consider the impact on the environment and the quality of the treated products. Wet-laid web formation is a non-woven web formation method, which is borrowed from the traditional papermaking industry. The principle is to open the fibers in the water medium into single fibers, mix different fiber raw materials, and make a fiber suspension slurry. The suspension slurry is transported to the web formation mechanism by water flow, and the fibers are formed into a web in a wet state and then reinforced into a non-woven fabric. This method has low cost and high recycling rate of waste cotton fibers. Compared with traditional wood pulp papermaking, cotton fiber papermaking has many advantages, such as good paper quality, high strength, good flexibility, and strong durability. However, if only cotton fiber is used as papermaking raw material, on the one hand, the strength of the paper depends only on the hydrogen bonding between the fibers, which will make the strength of the paper difficult to meet the actual use requirements. On the other hand, due to the poor antibacterial properties of cotton fibers, the functionality of the paper is poor, the economic benefits are low, and it is difficult to meet market demand. The traditional method of preparing antibacterial paper is mainly to post-treat it with antibacterial agents. The antibacterial effect of this treatment method is poor in durability, and more wastewater, waste gas and waste residue may be generated during the production process, and it is not environmentally friendly.
[0004] Patent CN107364195B discloses a method for preparing an antibacterial and restorative medical nonwoven fabric, the main components of which include tea fiber and bamboo fiber for antibacterial and deodorizing effects, acetate fiber for adhesion, and casein fiber and soy protein fiber for promoting wound healing. However, it still relies on adding pharmaceutical ingredients to the middle layer to achieve antibacterial effects and promote cell growth and skin healing. The presence of the middle layer directly affects the mechanical properties of the nonwoven fabric.
[0005] Patent CN115928436A discloses a degradable nonwoven fabric with physical sunscreen and soothing and antibacterial functions, the main components of which include: nano-scale physical sunscreen, polylactic acid fiber, carbon dioxide and propylene oxide copolymer, skin feel regulator, polylactic acid copolymer, natural fiber, soothing antibacterial agent and antibacterial adhesive. The materials required for preparation are complex, and although it has good antibacterial and sunscreen functions, the cost is relatively high. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing functional composite paper using waste cotton textiles, and in particular, to prepare a method for preparing degradable composite paper with antibacterial properties using waste cotton fibers combined with polylactic acid nanofibers. The present invention uses electrospinning technology to prepare polylactic acid nanofibers with antibacterial properties. On the one hand, polylactic acid nanofibers can effectively fill the gaps between fibers, melt under high temperature and high pressure conditions and bond with other fibers to enhance the mechanical properties of paper. On the other hand, the nanostructure can efficiently and stably seal the antibacterial substances therein, and has a broad-spectrum active, durable and drug-resistant antibacterial effect. In addition, both polylactic acid nanofibers and cotton fibers are green and degradable, so the use and treatment of the final product will not affect the environment. In order to improve the strength of the composite paper, expand its application scenarios, improve the economic benefits of the comprehensive utilization of waste textiles, and overcome the technical problem of low recycling rate of waste cotton textiles.
[0007] The present invention provides a method for preparing functional composite paper by using waste cotton textiles, comprising:
[0008] (1) mixing polylactic acid and a solvent to obtain a spinning solution, and electrospinning to obtain a polylactic acid nanofiber membrane;
[0009] Or polylactic acid and a solvent are mixed to obtain a spinning solution, and then an antibacterial agent is added to perform electrostatic spinning to obtain a polylactic acid nanofiber membrane;
[0010] (2) mixing cotton fiber, polylactic acid nanofiber membrane, and water, and shearing to obtain cotton fiber / polylactic acid nanofiber mixed pulp;
[0011] (3) The mixed pulp is used to prepare a wet fiber web, which is then hot-pressed to obtain a composite paper.
[0012] Preferably, the solvent in step (1) is one or more of chloroform, acetone, ethyl acetate, and dichloromethane;
[0013] Preferably, the antibacterial agent in step (1) is one or more of dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, and dodecyldimethylbenzylammonium chloride.
[0014] Preferably, in the step (1), the concentration of polylactic acid in the spinning solution is 6-15wt%; and the mass fraction of the antibacterial agent is 0.15% to 0.5%.
[0015] Preferably, the electrospinning process parameters in step (1) are as follows: the receiving distance of electrospinning is 10 to 20 cm, the spinning voltage is 10 to 20 kV, and the spinning speed is 0.5 to 1.5 ml / h.
[0016] Preferably, the cotton fibers in step (2) are cotton staple fibers, wherein the length of the cotton staple fibers is less than 10 mm.
[0017] The cotton staple fibers are pretreated from waste cotton textiles.
[0018] The waste cotton textiles are pretreated by opening and shearing the waste cotton textiles to obtain cotton staple fibers.
[0019] Preferably, in step (2), the mass ratio of the polylactic acid nanofiber membrane to the cotton staple fiber is 1:1 to 1:10.
[0020] Preferably, the shearing in step (2) is performed at 500 to 1000 r / min, using a high-speed shearing machine.
[0021] Preferably, in step (3), the mixed pulp is prepared into a wet fiber web as follows: the mixed pulp is prepared into a wet fiber web based on a wet-laid web-forming technology, wherein the process parameters of the wet-laid web-forming technology are as follows: the mesh size of the screen is 100 to 500 meshes, the suction force is 50 to 150 kPa, and the deposition time is 0.5 to 3 min.
[0022] The mixed pulp is deposited into a wet fiber web in a nonwoven wet-laid equipment.
[0023] Preferably, the hot pressing parameters in step (3) are: hot pressing temperature of 50 to 150° C., pressure of 0.5 to 5 GPa, and hot pressing time of 5 to 20 min.
[0024] The invention provides a composite paper prepared by the method.
[0025] The present invention provides an application of the composite paper in the field of food packaging paper. The composite paper has good mechanical properties and antibacterial properties, and can be used as food packaging paper, so that food can be less damaged during packaging. At the same time, the dense structure and antibacterial properties of the composite paper can isolate air and prevent food from being spoiled by microorganisms, effectively extending the shelf life of food.
[0026] The present invention utilizes polylactic acid nanofibers to replace traditional sizing materials. The polylactic acid nanofibers can effectively fill the gaps between cotton fibers and melt under high temperature and high pressure conditions to bond the surrounding fibers together, thereby improving the problem of poor mechanical properties of paper prepared by traditional papermaking processes.
[0027] The present invention uses electrostatic spinning technology to prepare a polylactic acid nanofiber membrane with antibacterial properties. By adding an antibacterial agent to the spinning solution, the antibacterial substance is efficiently and stably sealed in the nanostructure of the polylactic acid nanofiber, and finally mixed with waste cotton staple fibers for pulping to produce a composite paper with antibacterial properties. When bacteria come into contact with the paper, the antibacterial substance is slowly released from the composite paper and comes into contact with the bacteria, destroying the integrity of the bacterial cell membrane and producing an antibacterial effect.
[0028] The present invention uses waste cotton textiles as raw materials. First, the waste cotton textiles are simply physically dispersed to form short fibers; then, electrostatic spinning technology is used to prepare polylactic acid nanofiber membranes with antibacterial properties; mixed paper pulp of cotton short fibers / polylactic acid nanofibers is prepared by high-speed shearing; and finally, composite paper is obtained by wet web forming and hot pressing. The method uses polylactic acid nanofibers as antibacterial agent carriers and mixes them with cotton fibers, and hot pressing is used to enhance the fiber bonding effect. The process is simple, and the prepared composite paper has good mechanical properties, antibacterial properties and degradability.
[0029] Beneficial Effects
[0030] The present invention discloses a method for preparing composite paper with antibacterial properties by using waste cotton textiles. The present invention is low-cost and environmentally friendly. The polylactic acid nanofibers prepared by electrospinning are green and degradable and have a high specific surface area. The polylactic acid nanofibers are mixed with cotton staple fibers for pulping. On the one hand, the polylactic acid nanofibers can be used as antibacterial agent carriers to impart antibacterial properties to the materials. At the same time, the nanoscale polylactic acid fibers can be more effectively filled between the cotton fibers. During the hot pressing process, the melt flow acts as an adhesive to bond the fibers to each other, significantly improving the mechanical properties of the paper. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the microscopic morphology of the antibacterial composite paper;
[0032] Figure 2 It is a comparison chart of the antibacterial effect of Example (B) and Comparative Example (A). DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0034] For mechanical testing, a constant-rate tensile test method was used. The specimens were cut into 100 mm × 200 mm, and then fixed on the fixture of a universal testing machine. The specimens were stretched at a constant speed of 50 mm / min. Five specimens were selected for each sample for testing to obtain the average value.
[0035] Example 1
[0036] (1) Waste pure cotton fabric is cut into cotton staple fibers with a length of less than 5 mm using an opener and a shearing machine.
[0037] (2) 1 g of polylactic acid particles was dissolved in a dichloromethane solution to obtain a 10 wt% polylactic acid spinning solution, and 0.15 g of dodecyl dimethyl benzyl ammonium chloride was added to the spinning solution as an antibacterial agent for electrospinning. The electrospinning voltage was 17 kV, the receiving distance was 12 cm, and the spinning speed was 0.8 ml / h.
[0038] (3) The collected cotton staple fibers and the polylactic acid nanofiber membrane obtained by electrospinning are placed in deionized water, wherein the mass ratio of the cotton staple fibers to the polylactic acid nanofiber membrane is 3:1, and then pulped using a high-speed shearing machine at a rotation speed of 500 r / min to finally obtain cotton fiber / polylactic acid nanofiber mixed pulp.
[0039] (4) The deionized water in the mixed pulp is filtered out through a nonwoven wet-laid web-forming device, and the deposited fibers form a fiber web with uniform texture, which is then dried in a vacuum oven at 60°C for 0.5 h. The specific process parameters of the nonwoven wet-laid web-forming device are: the mesh size of the screen is 300 mesh, the suction force is 100 kPa, and the deposition time is 2 min.
[0040] (5) The fiber web was hot-pressed at a temperature of 100°C and a pressure of 1 GPa for 5 minutes to prepare an antibacterial composite paper.
[0041] Depend on Figure 1 The polylactic acid nanofibers shown are effectively filled between the cotton fibers. After hot pressing, the polylactic acid nanofibers melt and flow between the surface and the inside of the cotton staple fibers, acting as an adhesive, making the cotton staple fibers more tightly bonded, thereby improving the mechanical properties of the paper.
[0042] Example 2
[0043] (1) Waste pure cotton fabric is cut into cotton staple fibers with a length of less than 5 mm using an opener and a shearing machine.
[0044] (2) 1 g of polylactic acid particles was dissolved in a dichloromethane solution to obtain a 10 wt% polylactic acid spinning solution, and 0.15 g of dodecyl dimethyl benzyl ammonium chloride was added to the spinning solution as an antibacterial agent for electrospinning. The electrospinning voltage was 17 kV, the receiving distance was 12 cm, and the spinning speed was 0.8 ml / h.
[0045] (3) The recovered cotton staple fibers and the polylactic acid nanofiber membrane obtained by electrospinning are placed in deionized water, wherein the mass ratio of the cotton staple fibers to the polylactic acid nanofiber membrane is 4:1, and then pulped using a high-speed shearing machine at a rotation speed of 500 r / min to finally obtain cotton fiber / polylactic acid nanofiber mixed pulp.
[0046] (4) The deionized water in the mixed pulp is filtered out through a nonwoven wet-laid web-forming device, and the deposited fibers form a fiber web with uniform texture, which is then dried in a vacuum oven at 60°C for 0.5 h. The specific process parameters of the nonwoven wet-laid web-forming device are: the mesh size of the screen is 300 mesh, the suction force is 100 kPa, and the deposition time is 2 min.
[0047] (5) The fiber web was hot-pressed at a temperature of 100°C and a pressure of 1 GPa for 5 minutes to prepare an antibacterial composite paper.
[0048] Example 3
[0049] (1) Waste pure cotton fabric is cut into cotton staple fibers with a length of less than 5 mm using an opener and a shearing machine.
[0050] (2) 1 g of polylactic acid particles was dissolved in a dichloromethane solution to obtain a 10 wt% polylactic acid spinning solution, and 0.15 g of dodecyl dimethyl benzyl ammonium chloride was added to the spinning solution as an antibacterial agent for electrospinning. The electrospinning voltage was 17 kV, the receiving distance was 12 cm, and the spinning speed was 0.8 ml / h.
[0051] (3) The recovered cotton staple fibers and the polylactic acid nanofiber membrane obtained by electrospinning are placed in deionized water, wherein the mass ratio of the cotton staple fibers to the polylactic acid nanofiber membrane is 5:1, and then pulped using a high-speed shearing machine at a rotation speed of 500 r / min to finally obtain cotton fiber / polylactic acid nanofiber mixed pulp.
[0052] (4) The deionized water in the mixed pulp is filtered out through a nonwoven wet-laid web-forming device, and the deposited fibers form a fiber web with uniform texture, which is then dried in a vacuum oven at 60°C for 0.5 h. The specific process parameters of the nonwoven wet-laid web-forming device are: the mesh size of the screen is 300 mesh, the suction force is 100 kPa, and the deposition time is 2 min.
[0053] (5) The fiber web was hot-pressed at a temperature of 100°C and a pressure of 1 GPa for 5 minutes to prepare an antibacterial composite paper.
[0054] Example 4
[0055] (1) Waste pure cotton fabric is cut into cotton staple fibers with a length of less than 5 mm using an opener and a shearing machine.
[0056] (2) 1 g of polylactic acid particles was dissolved in a dichloromethane solution to obtain a 10 wt% polylactic acid spinning solution, and 0.15 g of dodecyl dimethyl benzyl ammonium chloride was added to the spinning solution as an antibacterial agent for electrospinning. The electrospinning voltage was 17 kV, the receiving distance was 12 cm, and the spinning speed was 0.8 ml / h.
[0057] (3) The recovered cotton staple fibers and the polylactic acid nanofiber membrane obtained by electrospinning are placed in deionized water, wherein the mass ratio of the cotton staple fibers to the polylactic acid nanofiber membrane is 6:1, and then pulped using a high-speed shearing machine at a rotation speed of 500 r / min to finally obtain cotton fiber / polylactic acid nanofiber mixed pulp.
[0058] (4) The deionized water in the mixed pulp is filtered out through a nonwoven wet-laid web-forming device, and the deposited fibers form a fiber web with uniform texture, which is then dried in a vacuum oven at 60°C for 0.5 h. The specific process parameters of the nonwoven wet-laid web-forming device are: the mesh size of the screen is 300 mesh, the suction force is 100 kPa, and the deposition time is 2 min.
[0059] (5) The fiber web was hot-pressed at a temperature of 100°C and a pressure of 1 GPa for 5 minutes to prepare an antibacterial composite paper.
[0060] Example 5
[0061] (1) Waste pure cotton fabric is cut into cotton staple fibers with a length of less than 5 mm using an opener and a shearing machine.
[0062] (2) 1 g of polylactic acid particles was dissolved in a dichloromethane solution to obtain a 10 wt% polylactic acid spinning solution, and 0.15 g of dodecyl dimethyl benzyl ammonium chloride was added to the spinning solution as an antibacterial agent for electrospinning. The electrospinning voltage was 17 kV, the receiving distance was 12 cm, and the spinning speed was 0.8 ml / h.
[0063] (3) The recovered cotton staple fibers and the polylactic acid nanofiber membrane obtained by electrospinning are placed in deionized water, wherein the mass ratio of the cotton staple fibers to the polylactic acid nanofiber membrane is 7:1, and then pulped using a high-speed shearing machine at a rotation speed of 500 r / min to finally obtain cotton fiber / polylactic acid nanofiber mixed pulp.
[0064] (4) The deionized water in the mixed pulp is filtered out through a nonwoven wet-laid web-forming device, and the deposited fibers form a fiber web with uniform texture, which is then dried in a vacuum oven at 60°C for 0.5 h. The specific process parameters of the nonwoven wet-laid web-forming device are: the mesh size of the screen is 300 mesh, the suction force is 100 kPa, and the deposition time is 2 min.
[0065] (5) The fiber web was hot-pressed at a temperature of 100°C and a pressure of 1 GPa for 5 minutes to prepare an antibacterial composite paper.
[0066] Comparative Example 1
[0067] The difference between Comparative Example 1 and Example 1 is that no polylactic acid nanofiber loaded with an antibacterial agent is added during pulping to obtain pure cotton fiber pulp, specifically:
[0068] (1) Waste pure cotton fabric is cut into cotton staple fibers with a length of less than 5 mm using an opener and a shearing machine.
[0069] (2) The recovered cotton staple fibers are placed in deionized water and then pulped using a high-speed shearing machine at a rotation speed of 500 r / min to finally obtain pure cotton fiber pulp.
[0070] (3) The deionized water in the mixed pulp is filtered out through a nonwoven wet-laid web-forming device, and the deposited fibers form a cotton fiber web with uniform texture, which is then dried in a vacuum oven at 60°C for 0.5 h. The specific process parameters of the nonwoven wet-laid web-forming device are: the mesh size of the screen is 300 mesh, the suction force is 100 kPa, and the deposition time is 2 min.
[0071] (4) The fiber web was hot-pressed at a temperature of 100°C and a pressure of 1 GPa for 5 minutes to prepare paper.
[0072] The tensile strength at break of the embodiment and the comparative example were tested using a universal testing machine. The results are shown in Table 1.
[0073] Table 1 Mechanical tests of examples and comparative examples
[0074] Examples Tensile strength(Mpa) Elongation at break (%) Example 1 57.3 22.1 Example 2 37.8 17.8 Example 3 26.1 15.6 Example 4 19.5 12.3 Example 5 17.2 11.4 Comparative Example 1 7.8 9.5
[0075] The antibacterial performance of paper can be determined by detecting the antibacterial zone. Figure 2 As shown, in the figure, A is comparative example 1 and B is embodiment 1.
[0076] From the above test results, it can be concluded that the nano-PLA fibers are filled between the cotton fibers and bonded to each other after hot pressing, which effectively improves the mechanical properties of the composite paper. In addition, the nano-PLA fibers loaded with antibacterial agents also give the composite paper antibacterial properties, showing good antibacterial properties.
Claims
1. A method for preparing a composite paper, comprising: (1) mixing polylactic acid and a solvent to obtain a spinning solution, and electrospinning to obtain a polylactic acid nanofiber membrane; Or polylactic acid and a solvent are mixed to obtain a spinning solution, and then an antibacterial agent is added to perform electrostatic spinning to obtain a polylactic acid nanofiber membrane; (2) mixing cotton fiber, polylactic acid nanofiber membrane, and water, and shearing to obtain mixed pulp; (3) The mixed pulp is used to prepare a wet fiber web, which is then hot-pressed to obtain a composite paper.
2. The preparation method according to claim 1, characterized in that: In step (1), the solvent is one or more of chloroform, acetone, ethyl acetate and dichloromethane; The antibacterial agent in step (1) is one or more of dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, and dodecyldimethylbenzylammonium chloride.
3. The preparation method according to claim 1, characterized in that: In the step (1), the concentration of polylactic acid in the spinning solution is 6-15wt%; The electrospinning process parameters in step (1) are as follows: the receiving distance of the electrospinning is 10 to 20 cm, the spinning voltage is 10 to 20 kV, and the spinning speed is 0.5 to 1.5 ml / h.
4. The preparation method according to claim 1, characterized in that: The cotton fibers in step (2) are short cotton fibers; The length of the cotton staple fibers is less than 10 mm.
5. The preparation method according to claim 4, characterized in that: The cotton staple fibers are obtained by opening and shearing waste cotton textiles.
6. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the polylactic acid nanofiber membrane to the cotton staple fiber is 1:1 to 1:
10.
7. The preparation method according to claim 1, characterized in that: The shearing in step (2) is performed at a speed of 500 to 1000 r / min.
8. The preparation method according to claim 1, characterized in that: In the step (3), the mixed pulp is prepared into a wet fiber web by: the mixed pulp is prepared into a wet fiber web based on a wet web forming technology, wherein the process parameters of the wet web forming technology are: the mesh size of the screen is 100 to 500 meshes, the suction force is 50 to 150 kPa, and the deposition time is 0.5 to 3 min; The hot pressing parameters in step (3) are: hot pressing temperature of 50 to 150° C., pressure of 0.5 to 5 GPa, and hot pressing time of 5 to 20 min.
9. A composite paper prepared by the method of claim 1.
10. Use of the composite paper according to claim 1 in the field of food packaging paper.
Citation Information
Patent Citations
A method for preparing an antibacterial and repairing medical nonwoven fabric
CN107364195B
Preparation method of degradable functional dressing
CN110507843A
Biodegradable non-woven fabric sheet prepared by recycling waste textiles and preparation method and application thereof
CN114000374A
Polylactic acid antibacterial composite fiber membrane as well as preparation method and application thereof
CN114182435A
Cellulose / polylactic acid fiber composite paper and preparation method thereof
CN114481681A